"Brothers-in-Law": Tracing the Descent of a Masonic Apron. (2nd January 2022) - Pass, Forrest D.
Abstract : A Masonic apron in the collection of the Canadian Museum of History has an unusual story: produced in rural Vermont in the 1820s, seven decades later it came into the possession of Ralph Lawton Broadbent, a Canadian civil servant and Mason. This research report proposes a biography for the apron in the intervening years and hints at the multiple possible meanings that Masons might attribute to their intriguing ceremonial garments. An esoteric symbol of lodge membership and fictive brotherhood, a Masonic apron also could symbolize other relationships; in this example, the apron appears to have descended to its final owner through a female line and thus may represent the bonds between fathers-in-law and sons-in-law